O trabalho de campo no Parque Urbano Municipal Itatiaia-Goiânia/GO: contribuições do percurso metodológico de mediação didática como meta para construção do pensamento geográfico no ensino de geografia - Silva, Wanessa Santos (2024)
Systematized Geography as a science assigns significant scientific and academic relevance to fieldwork as a methodological procedure. In school Geography, fieldwork is considered a teaching proposal that mobilizes various geographical themes. This research advocates the theoretical-methodological approach of fieldwork for teaching integrative geographical themes through didactic pathways for mediation in Geography education. This approach is supported by pedagogical knowledge, specifically the pedagogical content knowledge (Shulman, 2005), and the use of geographical problematizations to develop students’ ability to think geographically and act in their daily practices. The overall objective is to analyze the potential of fieldwork in an Urban Park to mobilize integrated knowledge of physical-natural and social components in education, aiming for the construction of geographical thinking. The specific objectives are: (i) to understand the theoretical-methodological concepts of fieldwork in an Urban Park in the didactic mediation process for Geography teaching; (ii) to relate fieldwork to the integration of physical-natural and social components; (iii) to recognize possibilities of thinking through Geography based on geographical situations, using them as aids for the construction of geographical thinking; and (iv) to evaluate the development and learning of students based on a theoretical-methodological concept of fieldwork, grounded in the construction of geographical thinking. The research justification unfolds on two levels: (a) personal/academic, emerging during undergraduate studies, noticing transformations in learning through fieldwork conducted in Geography studies, with the investigation beginning with a focus on teaching through the research conducted in the undergraduate final paper; (b) professional, present in teaching practice, with the opportunity to conduct fieldwork in Basic Education, confirming its potential in the teaching and learning process. It returns as an academic justification due to the desire to understand, from the perspective of a teacher-researcher, the potential of fieldwork in Geography education in an Urban Park. In this research, Urban Parks are conceived as linked to fieldwork and Geography education as a geographical situation due to the set of relationships in this space, understood as a product of influences between social and physical-natural components in the urban space. The research methodology is qualitative, specifically participant research with collaborative elements, allowing the confrontation of information between the object and the researched subject, facilitating the understanding of reality. The spatial scope of the research is the Itatiaia Municipal Park, located in the Itatiaia neighborhood, North region of Goiânia-GO. The subjects of this research are 8th-grade students from the State Military Police School of Goiás - Waldemar Mundim Unit, located in Vila Itatiaia, in the city of Goiânia-GO. It is concluded that the implementation of fieldwork in an Urban Park based on a theoretical-methodological concept is an effective strategy that allows the integration of daily life with geographical concepts and contents, promoting geographical thinking. Participatory fieldwork develops autonomy based on scientific research and helps solve problems in the studied urban space.